2016
DOI: 10.18564/jasss.3124
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Patterns in the Amount of Demand for Dental Visits: An Agent Based Modeling Approach

Abstract: There are some empirical evidences indicating that there is a collective complex oscillatory pattern in the amount of demand for dental visit at society level. In order to find the source of the complex cyclic behavior, we develop an agent-based model of collective behavior of routine dental check-ups in a social network. Simulation results show that demand for routine dental check-ups can follow an oscillatory pattern and the pattern's characteristics are highly dependent upon the structure of the social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…If individuals attended and had treatment, they would encourage others to attend. The analysis demonstrated that patterns associated with attendance had an oscillatory nature, and that the social structures in which individuals were embedded, as well as the number of effective connections within these structures, played a key role in influencing demand . Additionally, studies of dental behaviours and associations with friendship networks have also been conducted .…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…If individuals attended and had treatment, they would encourage others to attend. The analysis demonstrated that patterns associated with attendance had an oscillatory nature, and that the social structures in which individuals were embedded, as well as the number of effective connections within these structures, played a key role in influencing demand . Additionally, studies of dental behaviours and associations with friendship networks have also been conducted .…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The analysis demonstrated that patterns associated with attendance had an oscillatory nature, and that the social structures in which individuals were embedded, as well as the number of effective connections within these structures, played a key role in influencing demand. 75 Additionally, studies of dental behaviours and associations with friendship networks have also been conducted. 76 Initial research conducted among schoolchildren using questionnaires, and the statistical analysis of the data, was used to inform behaviour patterns for the agent-based model.…”
Section: Agent-based Modellingmentioning
confidence: 99%